The efficacy of cognitive behavioral therapy on reducing suicidal symptoms among adults: a systematic review and meta-analysis - Tong, Feng; Zhang, Yunxu; Jiao, Yang (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to systematically evaluate the effectiveness of cognitive behavioral therapy (CBT) on alleviating suicidal ideation, suicidal and self-harming behaviors, and depressive symptoms in adults.MethodsComprehensive searches were conducted in both English and Chinese databases including PubMed, PsycINFO, Cochrane Library, Web of Science, Embase, Scopus, CINAHL, HSE, ProQuest, CNKI, and Wanfang. Randomized controlled trials (RCTs) involving adults aged 18–65 years receiving CBT for suicidal symptoms were included. The primary outcome was suicidal ideation, while secondary outcomes included suicidal and self-harming behaviors and depressive symptoms. Risk of bias was assessed using the Cochrane Risk of Bias tool, and meta-analyses were conducted using a random-effects model. Subgroup analyses were performed based on follow-up duration (short-term ≤6 months, mid-term 6–12 months, long-term >12 months). Outcomes were reported using standardized mean differences (SMDs), odds ratios (ORs), and 95% confidence intervals (CIs).ResultsA total of 28 RCTs (n = 5,883) were included. In the short term, CBT significantly reduced suicidal ideation (SMD = −0.25, 95% CI: −0.34 to −0.16); however, no significant effects were observed at mid-term (SMD = −0.06, 95% CI: −0.24 to 0.12) or long-term (SMD = −0.18, 95% CI: −0.41 to 0.05) follow-up. CBT significantly reduced the risk of suicidal and self-harming behaviors across all follow-up durations (short-term OR = 0.72, 95% CI: 0.53 to 0.97; mid-term OR = 0.73, 95% CI: 0.54 to 0.98; long-term OR = 0.50, 95% CI: 0.31 to 0.80). CBT was also more effective than controls in improving depressive symptoms across all time points (short-term SMD = −0.36, 95% CI: −0.50 to −0.22; mid-term SMD = −0.26, 95% CI: −0.46 to −0.05; long-term SMD = −0.39, 95% CI: −0.56 to −0.21), with statistically significant differences.ConclusionCognitive behavioral therapy shows significant short-term benefits in reducing suicidal ideation and sustained effects in reducing suicidal/self-harming behaviors and improving depressive symptoms among adults. CBT may serve as an effective psychological intervention for suicide prevention in adults, although its long-term impact warrants further investigation.